A pilot study to explore the experiences of congenitally or early profoundly deafened candidates who receive cochlear implants as adults. (November 2015) - Jeffs, E.; Redfern, K.; Stanfield, C.; Starczewski, H.; Stone, S.; Twomey, T.; Fortnum, H.
Abstract : Objectives: To explore the experiences of congenitally or early profoundly deafened candidates who receive cochlear implants as adults. Methods: Eight congenitally or early profoundly deafened implantees who had received their implants as adults were interviewed using a semi-structured interview technique. Interviews were conducted in the participant's preferred communication mode (oral/aural, Sign Supported English, or British Sign Language). Results: All participants reported benefit from implantation. Areas of benefit identified correspond with results from similar studies conducted with post-lingually deafened adult implantees. Discussion: Congenitally or early profoundly deafened adults implanted as adults report benefit from cochlear implantation in the following areas: identity, hearing the world, and emotional wellbeing. They also commented on their motivation for wanting an implant and the advice they would give to others considering implantation.